1997
DOI: 10.1104/pp.115.3.971
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation of Wheat Mediated by Agrobacterium tumefaciens

Abstract: A rapid Agrobacferium fumefaciens-mediated transformation system for wheat was developed using freshly isolated immature embryos, precultured immature embryos, and embryogenic calli as explants. l h e explants were inoculated with a disarmed A. tumefaciens strain C58 (ABI) harboring the binary vector pMON18365 containing the p-glucuronidase gene with an intron, and a selectable marker, the neomycin phosphotransferase II gene. Various factors were found to influence the transfer-DNA delivery efficiency, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
352
2
9

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(384 citation statements)
references
References 28 publications
(40 reference statements)
21
352
2
9
Order By: Relevance
“…Danyang indicated that a half-strength N6 is the most efficient basal medium (data not shown). This is consistent with previous reports that the use of low-salt media during Agrobacterium infection improves T-DNA transformation (Cheng et al, 1997;Paz et al, 2004), although the mechanism of transformation enhancement is still unknown.…”
Section: Resultssupporting
confidence: 92%
“…Danyang indicated that a half-strength N6 is the most efficient basal medium (data not shown). This is consistent with previous reports that the use of low-salt media during Agrobacterium infection improves T-DNA transformation (Cheng et al, 1997;Paz et al, 2004), although the mechanism of transformation enhancement is still unknown.…”
Section: Resultssupporting
confidence: 92%
“…Nonionic surfactants improved the efficiency of transient Agrobacterium mediated transformation in wheat (Cheng et al 1997;Wu et al 2003) and Arabidopsis (Chung et al 2000;Kim et al 2009). In the present study also similar results on the effects of a surfactant, Tween 20 on transient GUS expression were obtained.…”
Section: Optimization Of Transformation Protocolmentioning
confidence: 99%
“…The addition of 0.03% Pluronic F68 to the inoculation medium (Cheng, et al, 1997) dramatically increased transient GUS expression by up to 100-fold (Table 4). Figure 5A shows that GUS staining in immature embryos varied from single spots to large patches of blue on the edge and scutelum, although GUS expression in immature embryos was not consistently observed in the same treatment and only about 40% of the experiments showed some GUS expression.…”
Section: Effect Of Pluronic F-68 On Gus Expressionmentioning
confidence: 99%
“…Cultures were collected with a scoop, suspended in inoculation medium (IM , Table 1), adjusted to the required optical density (λ = 600 nm) using a Spectronic 21D spectrophotometer (Milton Roy, USA) and used for inoculation within 30 min. In most of the experiments 0.03% (w/v) Pluronic F-68 was added to IM medium to try to improve transformation efficiency (Cheng et al 1997).…”
Section: Transformationmentioning
confidence: 99%
See 1 more Smart Citation